Reward Management Architecture and Employee Performance in Public Universities through Policies Processes Structures and Reward Categories - Beth Gathigia Gicheru; Rosemarie Wanyoike (Involvement International Journal of Business, 2026)
Reward practices are commonly studied as isolated mechanisms such as pay, incentives, or recognition, with limited attention to how reward policies, processes, structures, and categories operate as an integrated system. This study advances the concept of Reward Management Architecture (RMA) to explain how a coherent reward system influences employee performance in public universities. A descriptive cross-sectional survey was conducted among 129 administrative staff from two public universities in Nairobi County, Kenya. Data were collected using structured questionnaires and analyzed through descriptive statistics, Pearson correlation, and multiple regression analysis to examine the relationship between RMA dimensions and employee performance. All RMA dimensions recorded low mean scores (2.68–2.86), while employee performance indicators were also rated low (2.45–2.64). Strong positive correlations were observed between RMA components and performance (r = 0.720–0.777, p < 0.01). Regression results showed that RMA explains 78.9% of the variance in performance (R² = 0.789, p < 0.001), with reward structures (β = 0.297) and reward processes (β = 0.268) emerging as the strongest predictors. The findings indicate that employee performance is influenced more by the structural and procedural organization of rewards than by reward types. Interpreted through motivational and organizational theories, the study highlights the importance of fairness, clarity, and systemic coherence in reward management. The study contributes to human resource management literature by operationalizing RMA and offers practical insights for improving performance in public universities.